Electrolyte for preparing gel electrolyte, lithium battery and preparation method of lithium battery

By introducing flame retardant groups of vinyl and P-H bonds on the inorganic nanoparticles and adding them to the carbonate electrolyte to form a modified gel electrolyte, the thermal abuse and fire safety hazards that exist in lithium-ion batteries during use are solved, and the safety performance and thermal stability of the batteries are improved.

CN119638924APending Publication Date: 2025-03-18PHYLION BATTERY (CHUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411819779.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have thermal abuse and fire safety hazards during use, and the free flame retardant in the gel electrolyte has poor stability, which affects battery performance.

Method used

Modified inorganic nanoparticles are prepared by introducing vinyl groups and P-H bond-containing flame retardant groups on the inorganic nanoparticles, and added them to the carbonate electrolyte, combining polymeric monomers, initiators and lithium salts to form a gel electrolyte with flame retardant properties.

Benefits of technology

The safety performance and thermal stability of lithium batteries are significantly improved, and the negative impact of free flame retardants on electrochemical properties is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638924A_ABST
    Figure CN119638924A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte for preparing a gel electrolyte, a lithium battery and a preparation method of the lithium battery, and relates to the technical field of lithium batteries. The invention provides modified inorganic nanoparticles containing a vinyl group and a flame-retardant group containing a P-H bond, the modified inorganic nanoparticles, a polymeric monomer, an initiator and the like are introduced into the electrolyte, and the electrolyte provided by the embodiment of the invention is heated and cured to obtain the flame-retardant gel electrolyte. The safety performance and the thermal stability of the battery are obviously improved. In addition, the electrolyte provided by the invention can be polymerized in situ in a battery cell; the method is simple and efficient, does not influence the battery performance while ensuring the flame retardant property, is suitable for large-scale production, and provides a new thought for solving the safety problem of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to an electrolyte for preparing a gel electrolyte, a lithium battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, energy storage systems and other fields due to their high energy density and long cycle life. However, lithium-ion batteries have thermal abuse and fire safety hazards caused by short circuits, overcharging, overheating, etc. during use. Currently, commercial lithium-ion batteries still use traditional organic liquid electrolytes, which are flammable, explosive and easy to leak. They are also prone to generate lithium dendrites that pierce the diaphragm and cause battery short circuits, which also leads to major safety hazards in the battery.

[0003] Gel polymer electrolytes reduce production safety issues such as electrode corrosion and oxidative combustion caused by leakage of organic liquid electrolytes. Gel polymer electrolytes combine the advantages of high safety of solid polymer electrolytes and high ionic conductivity of liquid electrolytes to a certain extent, and are considered to be the most suitable electrolyte system for practical applications. Compared with liquid electrolytes, gel electrolytes are not easy to volatilize, have higher thermal stability and improved electrochemical stability. More importantly, gel electrolytes can be prepared by in-situ polymerization methods, which is compatible with the current most advanced lithium-ion battery manufacturing industry. Therefore, this method ensures that the electrodes are fully wetted by the liquid electrolyte before and after polymerization, which largely avoids the high interfacial resistance in batteries using traditional solid electrolytes.

[0004] Adding inorganic nanoparticles to the polymer matrix for modification can improve the comprehensive performance of polymer electrolytes. This is mainly reflected in the following aspects: (1) Inorganic nanoparticles can inhibit the orderly orientation of polymer chain segments in the polymer matrix and reduce crystallinity; (2) The large specific surface area of ​​nanoparticles can absorb more plasticizers, provide more three-dimensional transmission channels for lithium ion conduction, and significantly improve the ionic conductivity of polymer electrolytes; (3) Adding inorganic nanoparticles can also disperse stress and improve the mechanical strength of electrolytes; (4) Adding inorganic nanoparticles can improve the thermal stability and flame retardancy of polymer electrolytes; (5) Inorganic nanoparticles can also absorb acidic components generated during battery cycling and improve cycle stability. However, inorganic particles have poor dispersibility in polycarbonate polymers and are easy to agglomerate, which affects the electrical properties and safety performance of the entire polymer electrolyte.

[0005] Adding flame retardant additives can make organic electrolytes difficult to burn or non-flammable, improve the thermal stability of the electrolyte itself, and is a reliable and practical way to improve the safety of lithium-ion batteries. 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and its derivatives, as a halogen-free phosphorus-containing flame retardant, exhibit excellent flame retardant properties in polymers mainly through the mechanism of gas phase flame retardancy. Compared with halogen flame retardants, DOPO and its derivatives release very few corrosive and toxic gases during combustion. Therefore, many reactive and additive DOPO derivatives are favored by academia and industry, and their varieties are increasing. The PH bond in DOPO has strong reactivity and can react with compounds containing active double bonds (such as benzoquinone, acrylates, aldehydes and epoxy derivatives) to prepare reactive or additive flame retardants. However, studies have found that the stability of free DOPO flame retardants in electrolytes is poor, which has a greater impact on battery performance. For example, it affects the formation of the negative electrode SEI film, which in turn causes the exposed negative electrode active material to come into direct contact with the electrolyte and undergo a reduction reaction, generating a large amount of gas, and even causing graphite stripping, leading to a sharp deterioration of the lithium-ion battery. In addition, DOPO flame retardants are usually solid and have low solubility in the electrolyte, which limits their usage.

[0006] In summary, there is an urgent need to improve the gel electrolyte containing flame retardants in order to simultaneously improve the electrochemical properties and flame retardant properties of the battery and enhance the thermal stability of the battery.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The object of the present invention is to provide an electrolyte for preparing a gel electrolyte, a lithium battery and a preparation method thereof, aiming to simultaneously improve the electrochemical performance and thermal stability of the battery.

[0009] The present invention is achieved in that:

[0010] In a first aspect, the present invention provides an electrolyte for preparing a gel electrolyte, including a carbonate electrolyte, wherein the carbonate electrolyte contains modified inorganic nanoparticles, a polymerized monomer, an initiator and a lithium salt;

[0011] The modified inorganic nanoparticles contain vinyl groups and flame retardant groups containing PH bonds.

[0012] In an optional embodiment, the mass fraction of the modified inorganic nanoparticles is 0.5%-2.0%; preferably 0.8%-1.2%;

[0013] And / or, the modified inorganic nanoparticles are obtained by introducing vinyl groups and flame retardant groups containing PH bonds into inorganic nanoparticles, and the inorganic nanoparticles are selected from at least one of silicon dioxide nanoparticles, titanium dioxide nanoparticles and aluminum oxide nanoparticles;

[0014] and / or, the mass proportion of the flame retardant groups containing PH bonds on the modified inorganic nanoparticles is 1.6%-8%, and the mass proportion of the vinyl groups (CH2=CH2) is 0.16%-0.995%;

[0015] And / or, the flame retardant group containing a PH bond is a DOPO group.

[0016] In an optional embodiment, the mass fraction of the polymerized monomer is 5%-20%;

[0017] And / or, the polymerizable monomer is at least one selected from pentaerythritol triacrylate, propylene glycol methyl ether acetate, polyethylene glycol diacrylate and polyethylene glycol monomethyl ether acrylate.

[0018] In an optional embodiment, the mass fraction of the initiator is 0.001%-0.1%;

[0019] and / or, the initiator is a free radical initiator;

[0020] Preferably, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride and azobisisobutylimidazoline hydrochloride.

[0021] In an optional embodiment, the concentration of the lithium salt is 0.6 mol / L-2.5 mol / L, preferably 0.8 mol / L-1.5 mol / L;

[0022] And / or, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium bis(oxalatoborate), lithium oxalatodifluoroborate, lithium bis(fluorosulfonyl imide) and lithium bis(trifluoromethylsulfonyl imide); preferably, the lithium salt is lithium hexafluorophosphate.

[0023] In an optional embodiment, the carbonate electrolyte is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, fluorocarbonate and ethyl methyl carbonate;

[0024] Preferably, the carbonate electrolyte is a mixture of ethylene carbonate and dimethyl carbonate, and the volume ratio of ethylene carbonate to dimethyl carbonate is 1:(0.5-1.5).

[0025] In a second aspect, the present invention provides a method for preparing the electrolyte according to any one of the aforementioned embodiments, comprising:

[0026] preparing modified inorganic nanoparticles containing vinyl groups and flame retardant groups containing PH bonds;

[0027] The carbonate electrolyte, the modified inorganic nanoparticles, the polymerization monomer, the initiator and the lithium salt are mixed.

[0028] In an optional embodiment, the preparation process of the modified inorganic nanoparticles includes: firstly modifying the inorganic nanoparticles with a vinyl-containing silane compound to obtain modified nanoparticles, and then using a flame retardant containing a PH bond to react with the vinyl groups on the modified nanoparticles to prepare modified inorganic nanoparticles containing both vinyl groups and flame retardant groups with PH bonds;

[0029] Preferably, the vinyl-containing silane compound is selected from at least one of acryltrimethoxysilane, methylacryltrimethoxysilane and vinyltrimethoxysilane, and the molar ratio of the inorganic nanoparticles to the vinyl-containing silane compound is 1:(0.01-0.035);

[0030] Preferably, the molar ratio of the vinyl-containing silane compound to the PH bond-containing flame retardant is (1.5-3.0):1, more preferably (1.5-2.5):1;

[0031] Preferably, the preparation process of the modified inorganic nanoparticles comprises: mixing the dried inorganic nanoparticles, the vinyl-containing silane compound and the first organic solvent, adjusting the pH value to 9-11, reacting at 65°C-80°C for 10h-15h, removing the first organic solvent after the reaction is completed to obtain modified nanoparticles; mixing the modified nanoparticles, the flame retardant containing the PH bond and the second organic solvent, heating to 70°C-90°C to dissolve the flame retardant containing the PH bond, dripping the initiator solution into the reaction system for 1.5h-3.0h, continuing the reaction for 10h-15h, and removing the second organic solvent after the reaction is completed;

[0032] More preferably, the first organic solvent is selected from at least one of anhydrous ethanol and anhydrous methanol;

[0033] More preferably, the second organic solvent is selected from at least one of toluene and xylene;

[0034] More preferably, the initiator solution is obtained by mixing the initiator and the second organic solvent, and the mass ratio of the initiator to the flame retardant containing a PH bond is (0.3-1.0):100.

[0035] In a third aspect, the present invention provides a method for preparing a lithium battery, comprising: injecting the electrolyte of any one of the aforementioned embodiments or the electrolyte prepared by any one of the preparation methods of the aforementioned embodiments into a battery cell, encapsulating it into a liquid battery, and heating the liquid battery;

[0036] Preferably, during the heating process, the heating temperature is controlled to be 40°C-80°C, and the treatment time is 0.5h-10h;

[0037] Preferably, the battery cell is assembled by stacking a positive electrode sheet, a separator and a negative electrode sheet;

[0038] Preferably, the positive electrode active material on the positive electrode plate is a nickel-cobalt-manganese-lithium ternary material;

[0039] Preferably, the isolation film is a PP film;

[0040] Preferably, the negative electrode active material on the negative electrode sheet is graphite.

[0041] In a fourth aspect, the present invention provides a lithium battery prepared by the preparation method of the aforementioned embodiment.

[0042] The present invention has the following beneficial effects: the present invention provides modified inorganic nanoparticles containing vinyl groups and flame retardant groups containing PH bonds, introduces the modified inorganic nanoparticles, polymerized monomers, initiators, etc. into an electrolyte, and obtains a gel electrolyte with flame retardant properties after heating and curing the electrolyte provided by an embodiment of the present invention, which significantly improves the safety performance and thermal stability of the battery. In addition, the gel electrolyte formed by the electrolyte provided by the present invention does not contain free flame retardant groups and will not affect the electrochemical performance of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0044] Figure 1 Schematic diagram of modification of SiO2 nanoparticles with DOPO groups and vinyl groups in the present invention;

[0045] Figure 2 This is a schematic diagram of the morphology of the solidified gel electrolyte containing 1 wt% modified SiO2 in the present invention;

[0046] Figure 3 It is a normal temperature cycle diagram of the electrolyte after the modified SiO2 and the unmodified SiO2 are solidified in the present invention;

[0047] Figure 4 It is a high temperature cycle diagram of the electrolyte after the modified SiO2 and unmodified SiO2 are solidified in the present invention. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0049] The embodiment of the present invention provides an electrolyte for preparing a gel electrolyte, including a carbonate electrolyte, wherein the carbonate electrolyte contains modified inorganic nanoparticles, a polymerized monomer, an initiator and a lithium salt; wherein the modified inorganic nanoparticles contain vinyl groups and flame retardant groups containing PH bonds.

[0050] It should be noted that the electrolyte provided in the embodiment of the present invention can be heated and polymerized to generate a gel electrolyte after being injected into the battery cell. The modified inorganic nanoparticles introduced into the electrolyte contain vinyl groups and flame retardant groups containing PH bonds. The PH bonds are active and can undergo substitution and addition reactions with a variety of substances. A variety of functional monomers can be synthesized through structural design. The introduced flame retardant groups can inhibit combustion and improve the safety performance of the battery.

[0051] In some embodiments, the mass fraction of the modified inorganic nanoparticles is 0.5%-2.0%; preferably 0.8%-1.2%. The mass fraction of the modified inorganic nanoparticles in the electrolyte is preferably within the above range. Too little introduction will not have a good flame retardant effect, and too much introduction will affect the electrochemical performance of the battery. Specifically, in the electrolyte, the mass fraction of the modified inorganic nanoparticles can be 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, etc.

[0052] Further, the modified inorganic nanoparticles are obtained by introducing vinyl groups and flame retardant groups containing PH bonds into inorganic nanoparticles, the inorganic nanoparticles are selected from at least one of silicon dioxide nanoparticles, titanium dioxide nanoparticles and aluminum oxide nanoparticles, and the inorganic nanoparticles can be any one or more of the above. The flame retardant group containing PH bonds is a DOPO group, but is not limited thereto. The mass proportion of DOPO groups on the modified inorganic nanoparticles is 1.6%-8% (such as 1.6%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, etc.), and the mass proportion of vinyl groups (CH2=CH2) is 0.16%-0.995% (such as 0.160%, 0.200%, 0.300%, 0.400%, 0.500%, 0.600%, 0.700%, 0.800%, 0.900%, 0.995%, etc.).

[0053] Specifically, the electrolyte additive of the present invention has a DOPO structure, and its structure is as follows:

[0054]

[0055] The structure contains biphenyl ring and phenanthrene ring structure. The cyclic O=P—O bond has higher thermal stability and chemical stability than general, non-cyclic organic phosphates, and better flame retardancy. In addition, the PH bond is active and can undergo substitution and addition reactions with a variety of substances. A variety of functional monomers can be synthesized through structural design. The DOPO structure contains the P element and has excellent flame retardant effect. In the case of overheating and combustion of the battery, PO· is formed, which can combine with H· and HO· free radicals in the flame area to inhibit combustion and improve the safety of the battery. In addition, the DOPO structure contains biphenyl ring and phenanthrene ring structure, and the cyclic O=P—O bond has better thermal stability and flame retardancy.

[0056] In some embodiments, the mass fraction of the polymerized monomer is 5%-20%, such as 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc. The polymerized monomer is selected from at least one of pentaerythritol triacrylate, propylene glycol methyl ether acetate, polyethylene glycol diacrylate and polyethylene glycol monomethyl ether acrylate, and the polymerized monomer can be any one or more of the above monomers, which can be heated and polymerized at a relatively low temperature to achieve the preparation of the gel electrolyte.

[0057] In some embodiments, the mass fraction of the initiator is 0.001%-0.1%, such as 0.001%, 0.005%, 0.010%, 0.030%, 0.050%, 0.080%, 0.100%, etc. The initiator is a commonly used free radical initiator, and the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride and azobisisobutylimidazoline hydrochloride. The initiator can be any one or more of the above, and can initiate the polymerization reaction of the polymerization monomer.

[0058] In some embodiments, the concentration of the lithium salt is 0.6mol / L-2.5mol / L, preferably 0.8mol / L-1.5mol / L, such as 0.6mol / L, 0.8mol / L, 1.0mol / L, 1.3mol / L, 1.5mol / L, 1.8mol / L, 2.0mol / L, 2.3mol / L, 2.5mol / L, etc. The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium bisoxalate borate, lithium oxalate difluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide. The lithium salt can be any one or more of the above, preferably lithium hexafluorophosphate. The lithium hexafluorophosphate raw material is easy to obtain, and the comprehensive performance of the electrolyte is more excellent.

[0059] In some embodiments, the carbonate electrolyte is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, fluorocarbonate and ethyl methyl carbonate, and the carbonate electrolyte can be any one or more of the above. Preferably, the carbonate electrolyte is a mixture of ethylene carbonate and dimethyl carbonate, and the volume ratio of ethylene carbonate to dimethyl carbonate is 1: (0.5-1.5), such as 1: 0.5, 1: 0.8, 1: 1.0, 1: 1.2, 1: 1.5, etc. It is advisable to use a mixed solvent of ethylene carbonate and dimethyl carbonate, which can further improve the performance of the electrolyte.

[0060] The present invention provides a method for preparing an electrolyte, the steps of which are as follows:

[0061] S1. Preparation of modified inorganic nanoparticles

[0062] Modified inorganic nanoparticles containing vinyl groups and flame retardant groups containing PH bonds are prepared by first introducing the vinyl groups and then introducing the flame retardant groups containing PH bonds.

[0063] In some embodiments, the preparation process of modified inorganic nanoparticles includes: firstly modifying inorganic nanoparticles using a vinyl-containing silane compound to obtain modified nanoparticles, and then using a flame retardant containing a PH bond to react with the vinyl groups on the modified nanoparticles to prepare modified inorganic nanoparticles containing both vinyl groups and flame retardant groups with PH bonds.

[0064] It should be noted that the flame retardant containing a PH bond can be 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), and a gel electrolyte containing a DOPO flame retardant is prepared, wherein the advantages of adding modified nanoparticles are obvious: first, it has good dispersibility, which solves the problem of difficult dispersion and agglomeration in polymer macromolecules, and the retained vinyl group can further participate in the polymerization of propylene-based monomers; second, the DOPO with excellent flame retardancy is fixed on the modified SiO2 nanoparticles, and there will be no free DOPO affecting the electrical performance of the lithium-ion battery.

[0065] It should be noted that the agglomerates of silica before modification are formed during its preparation process. Each silica agglomerate is composed of countless fine particles. There are many -OH groups distributed on the surface of each fine wet particle. During the drying process, the -OH groups on the surface of adjacent particles are dehydrated and agglomerated together. However, after grafting modification, the hydrophobic groups -OCH3, H, =CH- are introduced on its surface, making it difficult for SiO2 particles to be adsorbed and agglomerated. The modified three-dimensional network structure is as follows: Figure 1 shown.

[0066] In some embodiments, the vinyl-containing silane compound is selected from at least one of acryltrimethoxysilane, methylacryltrimethoxysilane and vinyltrimethoxysilane, and the vinyl-containing silane compound can be any one or more of the above, preferably vinyltrimethoxysilane (VTS); the molar ratio of the inorganic nanoparticles to the vinyl-containing silane compound is 1:(0.01-0.035); the molar ratio of the vinyl-containing silane compound to the flame retardant containing a PH bond is (1.5-3.0):1, more preferably (1.5-2.5):1. By adjusting the amount of inorganic nanoparticles, vinyltrimethoxysilane and flame retardant containing a PH bond, the amount of vinyl and flame retardant groups containing a PH bond introduced into the obtained modified inorganic nanoparticles is more appropriate, which can significantly improve the safety performance of the battery while ensuring the electrochemical performance of the battery.

[0067] Specifically, the molar ratio of the inorganic nanoparticles and the vinyl-containing silane compound can be 1:0.01, 1:0.015, 1:0.02, 1:0.025, 1:0.03, 1:0.035, etc.; the molar ratio of the vinyl-containing silane compound and the PH bond-containing flame retardant can be 1.5:1, 1.8:1, 2.0:1, 2.2:1, 2.3:1, 2.5:1, 2.8:1, 3.0:1, etc.

[0068] Further, the preparation process of the modified inorganic nanoparticles includes: mixing the dried inorganic nanoparticles, the vinyl-containing silane compound and the first organic solvent, adjusting the pH value to 9-11, reacting at 65°C-80°C for 10h-15h, removing the first organic solvent after the reaction is completed, and obtaining the modified nanoparticles; mixing the modified nanoparticles, the flame retardant containing the PH bond and the second organic solvent, heating to 70°C-90°C to dissolve the flame retardant containing the PH bond, dripping the initiator solution into the reaction system, the dripping time is 1.5h-3.0h, continuing the reaction for 10h-15h, and removing the second organic solvent after the reaction is completed. First, the vinyl-containing silane compound (such as vinyl trimethoxysilane) is used to react with the hydroxyl group in the solution under alkaline conditions to introduce vinyl groups on the inorganic nanoparticles, and then the flame retardant containing the PH bond (such as DOPO) is used to react with part of the vinyl groups on the modified nanoparticles to prepare SiO2 nanoparticles containing both DOPO groups and vinyl groups.

[0069] Specifically, before modification, the inorganic nanoparticles can be dried by vacuum drying, and the drying temperature can be controlled to be about 100°C-110°C, and the drying time can be 5h-10h. In the first step of modification, the pH value can be adjusted to 9-11 with ammonia water, such as 9, 10, 11, etc.; the reaction temperature of the first step reaction can be 65°C, 70°C, 75°C, 80°C, etc., and the reaction time can be 10h, 11h, 12h, 13h, 14h, 15h, etc., and the first organic solvent can be removed by rotary evaporation. The reaction temperature of the reaction with the flame retardant containing PH bond can be 70°C, 80°C, 90°C, etc., the initiator solution dropwise addition time can be 1.5h, 2.0h, 2.5h, 3.0h, etc., the reaction time can be 10h, 11h, 12h, 13h, 14h, 15h, etc., and the second organic solvent can be removed by rotary evaporation.

[0070] Furthermore, the first organic solvent is selected from at least one of anhydrous ethanol and anhydrous methanol, and the first organic solvent can be any one or more of the above; the second organic solvent is selected from at least one of toluene and xylene, and the second organic solvent can be any one or more of the above.

[0071] Further, the initiator solution is obtained by mixing the initiator and the second organic solvent, and the mass ratio of the initiator to the flame retardant containing the PH bond is (0.3-1.0):100. The amount of the initiator is preferably within the above range, which can better initiate the polymerization reaction and allow the reaction to proceed fully. Specifically, the mass ratio of the initiator to the flame retardant containing the PH bond can be 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100, 1.0:100, etc.

[0072] S2. Preparation of electrolyte

[0073] The carbonate electrolyte, modified inorganic nanoparticles, polymerization monomer, initiator and lithium salt are mixed to obtain an electrolyte for use. The specific types and amounts of the carbonate electrolyte, polymerization monomer, initiator and lithium salt can be referred to the above description and will not be repeated here.

[0074] An embodiment of the present invention provides a method for preparing a lithium battery, comprising: injecting the electrolyte provided by the embodiment of the present invention into a battery cell, packaging it into a liquid battery, and heating the liquid battery to polymerize the polymerization monomers.

[0075] In some embodiments, during the heating process, the heating temperature is controlled to be 40°C-80°C, and the treatment time is 0.5h-10h. By adjusting the heating treatment conditions of the assembled liquid battery, the polymerized monomers are fully reacted to form a gel electrolyte. Specifically, the heating temperature can be 40°C, 50°C, 60°C, 70°C, 80°C, etc., and the treatment time can be 0.5h, 1.0h, 3.0h, 5.0h, 8.0h, 10.0h, etc.

[0076] It should be noted that the mass fraction of modified inorganic nanoparticles in the electrolyte provided by the embodiment of the present invention is 0.5%-2.0%; preferably 0.8%-1.2%, the amount of modified SiO2 is small, it can be evenly dispersed, and the effect is significant; the one-pot in-situ polymerization is simple and efficient, and the prepared gel electrolyte battery has excellent electrical properties and greatly improved safety performance. The gel electrolyte has a high electrochemical window, high ionic conductivity and excellent flame retardant properties. The modified SiO2 is fixed and evenly dispersed in the polymer matrix after polymerization. Compared with liquid electrolyte lithium-ion batteries, the lithium-ion batteries prepared based on this gel electrolyte have superior electrical properties and obvious safety performance advantages.

[0077] Furthermore, the battery cell is assembled by stacking the positive electrode sheet, the separator and the negative electrode sheet to form a positive electrode / separator / negative electrode structure. The types of the positive electrode sheet, the separator and the negative electrode sheet are not limited, and they can all be common accessories for commercially available lithium batteries. For example, the positive electrode active material on the positive electrode sheet can be a nickel-cobalt-manganese-lithium ternary material, but is not limited thereto; the separator can be a PP dry film, but is not limited thereto; the negative electrode active material on the negative electrode sheet can be graphite, such as natural graphite, but is not limited thereto.

[0078] An embodiment of the present invention provides a lithium battery, which is prepared by the preparation method provided by the embodiment of the present invention. The battery has a gel electrolyte with excellent flame retardant properties and no free flame retardant particles, and can significantly improve the safety performance and high-temperature cycle performance of the battery.

[0079] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0080] Example 1

[0081] This embodiment provides a method for preparing a lithium battery, the steps are as follows:

[0082] (1) Preparation of modified nano-SiO2 with DOPO groups and vinyl groups

[0083] Take nano-SiO2 (average particle size is about 10 nm) and dry it in a vacuum oven at 105°C for 8 h for later use.

[0084] Weigh 129.6g (2.16mol) of dried SiO2 and 8.88g (0.06mol) of vinyltrimethoxysilane (VTS), put them into a 2000mL three-necked flask, and then add 1000mL of anhydrous ethanol to the three-necked flask. Move the three-necked flask into an oil bath, adjust the pH of ammonia water to 10, introduce N2 gas as a protective gas, and react for 12h at the reflux temperature of ethanol (reflux temperature is 78℃). After the reaction is completed, ethanol is evaporated. Then add 6.48g (0.03mol) of DOPO and 500mL of toluene, and heat to 80℃ under N2 gas protection and mechanical stirring. When DOPO is completely dissolved, dissolve 0.02g of azobisisobutyronitrile (AIBN) in 50mL of toluene and drip it into the reaction system within 2h. The reaction was then continued at 80° C. for 12 h and then stopped. The toluene was removed by rotary evaporation to obtain modified nano-SiO2 containing both DOPO groups and vinyl groups.

[0085] Note: In Example 1, the molar ratio of SiO2, vinyltrimethoxysilane, and DOPO is 1:0.0278:0.0139.

[0086] (2) Preparation of electrolyte

[0087] 1wt% modified nano-SiO2, 5wt% pentaerythritol triacrylate, 4.995wt% polyethylene glycol diacrylate, 0.005wt% AIBN, and 89wt% carbonate electrolyte (1 mol / L lithium hexafluorophosphate, ethylene carbonate and dimethyl carbonate solvents mixed in a volume ratio of 1:1) were mixed evenly and set aside.

[0088] (3) Preparation of pure ternary battery cells (14Ah):

[0089] Prepare nickel-cobalt-manganese-lithium positive electrode sheets, and purchase 6-series nickel-cobalt-manganese positive electrode sheets model TLD6507 from Tianli Lithium Energy Company.

[0090] Prepare a PP isolation film, purchased from Huiqiang New Materials Co., Ltd. Dry-process isolation film, with a thickness of 25 μm.

[0091] Prepare a graphite negative electrode sheet purchased from Sno New Materials Co., Ltd., model SN-4D-1.

[0092] The nickel-cobalt-manganese-lithium positive electrode sheet, the PP separator, and the graphite negative electrode sheet are stacked in sequence to form a positive electrode / separator / negative electrode structure, and then the electrolyte in step (2) is injected into the battery cell, which is packaged to form a liquid battery; the assembled liquid battery is heated at 70° C. for 0.5 h to solidify the polymer electrolyte precursor solution to obtain a gel electrolyte battery cell.

[0093] The electrolyte obtained in step (2) of Example 1 was solidified in a glass bottle. The specific steps are as follows: the electrolyte was placed in a glass bottle and the bottle was tightly covered. Then the electrolyte was kept at 75°C for 1 hour to obtain a gel electrolyte. Figure 2 It can be seen that the gel electrolyte formed in this embodiment is evenly dispersed.

[0094] Example 2

[0095] The only difference from Example 1 is that in step (1), the amount of nano-SiO2 remains unchanged, and the molar ratio of SiO2, vinyltrimethoxysilane and DOPO is 1:0.0278:0.0046.

[0096] Example 3

[0097] The only difference from Example 1 is that in step (1), the amount of nano-SiO2 remains unchanged, and the molar ratio of SiO2, vinyltrimethoxysilane and DOPO is 1:0.0278:0.0092.

[0098] Example 4

[0099] The only difference from Example 1 is that in step (1), the amount of nano-SiO2 remains unchanged, and the molar ratio of SiO2, vinyltrimethoxysilane and DOPO is 1:0.0278:0.0185.

[0100] Example 5

[0101] The only difference from Example 1 is that in step (2), the mass fraction of modified nano-SiO2 is 0.3%, the amount of carbonate electrolyte is adjusted accordingly, and the mass fractions of other components (monomer, initiator, lithium salt concentration, etc.) are kept unchanged.

[0102] Example 6

[0103] The only difference from Example 1 is that in step (2), the mass fraction of modified nano-SiO2 is 0.5%, the amount of carbonate electrolyte is adjusted accordingly, and the mass fractions of other components (monomer, initiator, lithium salt concentration, etc.) are kept unchanged.

[0104] Example 7

[0105] The only difference from Example 1 is that in step (2), the mass fraction of modified nano-SiO2 is 1.5%, the amount of carbonate electrolyte is adjusted accordingly, and the mass fractions of other components (monomer, initiator, lithium salt concentration, etc.) are kept unchanged.

[0106] Example 8

[0107] The only difference from Example 1 is that in step (2), the mass fraction of modified nano-SiO2 is 2.0%, the amount of carbonate electrolyte is adjusted accordingly, and the mass fractions of other components (monomer, initiator, lithium salt concentration, etc.) are kept unchanged.

[0108] Example 9

[0109] The only difference from Example 1 is that in step (2), the mass fraction of modified nano-SiO2 is 3.0%, the amount of carbonate electrolyte is adjusted accordingly, and the mass fractions of other components (monomer, initiator, lithium salt concentration, etc.) are kept unchanged.

[0110] Example 10

[0111] The only difference from Example 1 is that in step (1), DOPO is replaced by an equal molar amount of DOPO with a methyl group on the benzene ring.

[0112] Embodiment 11

[0113] The only difference from Example 1 is that in step (1), vinyltrimethoxysilane is replaced by an equimolar amount of acryltrimethoxysilane.

[0114] Comparative Example 1

[0115] The only difference from Example 1 is that step (1) is not performed, and unmodified SiO2 nanoparticles are added to the electrolyte in an amount consistent with that in Example 1.

[0116] The electrolyte obtained in Comparative Example 1 was solidified in a glass bottle, and the specific steps were as follows: the electrolyte was placed in a glass bottle and tightly covered. Then, the temperature was kept at 75°C for 1 hour to obtain a gel electrolyte. It can be seen that although it is also a gel, many white agglomerates appear, which is the result of the easy agglomeration of unmodified SiO2 nanoparticles.

[0117] Comparative Example 2

[0118] The difference from Example 1 is that the steps of preparing modified nano-SiO2 in step (1) are different, specifically as follows:

[0119] Directly weigh 129.6g (2.16mol) of dried SiO2 into a 2000mL three-necked flask, then add 6.48g (0.03mol) DOPO and 500mL toluene, and heat to 80°C under N2 gas protection and mechanical stirring. After DOPO is completely dissolved, 0.02g of azobisisobutyronitrile (AIBN) is dissolved in 50mL toluene and dripped into the reaction system within 2h. After that, the reaction is continued at 80°C for 12h, and then the reaction is stopped and the toluene is removed by rotary evaporation. However, after drying, a uniform powder was not obtained, but blocky DOPO appeared. This shows that the feasibility of this method is low and DOPO cannot be grafted onto nano-SiO2.

[0120] Note: In Comparative Example 2, the molar ratio of SiO2 to DOPO is 1:0.0138.

[0121] Test Example 1

[0122] The flame retardant performance, safety performance and cycle performance of the batteries prepared in the test examples and comparative examples were tested.

[0123] (1) Flame retardancy test: Take a small amount of the modified SiO2 gel electrolyte of Example 1 and use fire to ignite it. The result is that it cannot ignite, which confirms its excellent flame retardancy. However, the 1wt% SiO2 gel electrolyte of Comparative Example 1 is ignited and ignites immediately. The gel electrolytes of Examples 4, 7, 8, 9, 10 and 11 cannot be ignited. However, the gel electrolytes of Examples 2 and 3 are extinguished 2 seconds after ignition, the gel electrolyte of Example 5 is extinguished 5 seconds after ignition, and the gel electrolyte of Example 6 is extinguished 3 seconds after ignition. This is because the modified nanoparticles of Examples 2 and 3 contain less DOPO than those of Examples 1 and 4. The gel electrolyte of Example 5 contains only 0.3wt% modified SiO2, and the gel electrolyte of Example 6 contains 0.5wt% modified SiO2.

[0124] (2) Test conditions for electrical performance and safety performance: test the performance after overcharging, hot box, and needle puncture, as shown in Table 1.

[0125] Table 1 Performance test results of lithium batteries prepared in Examples and Comparative Examples

[0126]

[0127] It can be seen that Example 1 benefits from the uniform distribution of modified SiO2 and its DOPO flame retardant group, and all the cells based on modified SiO2 gel electrolyte pass overcharging, hot box and acupuncture. Modified SiO2 is a nano flame retardant, which is evenly distributed in the electrolyte. It can effectively utilize the particles to easily capture free radicals released by the combustion reaction and improve the flame retardant performance. Moreover, there is a flame retardant synergistic effect between the phosphorus in DOPO and the silicon in SiO2, which promotes the formation of a denser and expanded carbon layer, thereby effectively reducing the release of heat and smoke. During combustion, the particles can also be used to form a dense and uniform barrier layer on the surface of the material when burning. Therefore, the modified SiO2 gel electrolyte significantly improves the safety performance of the battery cell.

[0128] (3) The normal temperature cycle diagram and high temperature cycle diagram of the electrolyte after the modified SiO2 and unmodified SiO2 solidification were tested, see Figure 3 and Figure 4 .

[0129] Normal temperature cycle test method: let the lithium-ion battery stand for 30 minutes at 25℃, charge it to 4.2V with 1C constant current, then charge it to 0.05C with constant voltage 4.2V, and then discharge it to 2.7V with 1C constant current. Record the discharge capacity at this time and the discharge capacity of the first cycle. Let it stand for 10 minutes, continue to charge it to 4.2V with 1C constant current, then charge it to 0.05C with constant voltage 4.2V, and then discharge it to 2.7V with 1C constant current. Repeat this cycle and record the capacity of the lithium-ion battery in each cycle; the capacity retention rate of the nth cycle = the discharge capacity of the nth cycle / the discharge capacity of the first cycle.

[0130] High temperature cycle test method: at 45°C, other operations are the same as at normal temperature.

[0131] like Figure 3 As shown in the figure, under normal temperature cycling, the battery cell based on modified SiO2-gel electrolyte has advantages over SiO2-gel electrolyte, and can last more than 100 cycles at 80% capacity. This is because SiO2 is easy to agglomerate, resulting in uneven distribution in the electrolyte, which will affect the cycle performance of the battery. However, modified SiO2 is not easy to agglomerate and is evenly distributed in the electrolyte, making lithium ion conduction more uniform and smooth, and the cycle performance is good.

[0132] like Figure 4 As shown in the figure, under high temperature cycling, the battery cell based on modified SiO2-gel electrolyte has obvious advantages over SiO2-gel electrolyte. This is because SiO2 is easy to agglomerate and unevenly distributed in the electrolyte, resulting in electrolyte stress and uneven distribution of electrolyte, which intensifies the side reactions under high temperature cycling, thus affecting its high temperature cycling performance. The modified SiO2 is evenly distributed in the electrolyte, making the lithium ion conduction more uniform and smooth, the current density in each part is also uniform, and the cycling performance is good.

[0133] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An electrolyte for preparing a gel electrolyte, characterized in that: The invention comprises a carbonate electrolyte, wherein the carbonate electrolyte contains modified inorganic nanoparticles, a polymerizable monomer, an initiator and a lithium salt; The modified inorganic nanoparticles contain vinyl groups and flame retardant groups containing PH bonds.

2. The electrolyte according to claim 1, characterized in that The mass fraction of the modified inorganic nanoparticles is 0.5%-2.0%; preferably 0.8%-1.2%; And / or, the modified inorganic nanoparticles are obtained by introducing vinyl groups and flame retardant groups containing PH bonds into inorganic nanoparticles, and the inorganic nanoparticles are selected from at least one of silicon dioxide nanoparticles, titanium dioxide nanoparticles and aluminum oxide nanoparticles; and / or, the mass proportion of the flame retardant groups containing PH bonds on the modified inorganic nanoparticles is 1.6%-8%, and the mass proportion of the vinyl groups is 0.16%-0.995%; And / or, the flame retardant group containing a PH bond is a DOPO group.

3. The electrolyte according to claim 1, characterized in that The mass fraction of the polymerization monomer is 5%-20%; And / or, the polymerizable monomer is at least one selected from pentaerythritol triacrylate, propylene glycol methyl ether acetate, polyethylene glycol diacrylate and polyethylene glycol monomethyl ether acrylate.

4. The electrolyte according to claim 1, characterized in that The mass fraction of the initiator is 0.001%-0.1%; and / or, the initiator is a free radical initiator; Preferably, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride and azobisisobutylimidazoline hydrochloride.

5. The electrolyte according to claim 1, characterized in that The concentration of the lithium salt is 0.6 mol / L-2.5 mol / L, preferably 0.8 mol / L-1.5 mol / L; And / or, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium bis(oxalatoborate), lithium oxalatodifluoroborate, lithium bis(fluorosulfonyl imide) and lithium bis(trifluoromethylsulfonyl imide); preferably, the lithium salt is lithium hexafluorophosphate.

6. The electrolyte according to claim 1, characterized in that The carbonate electrolyte is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, fluorocarbonate and ethyl methyl carbonate; Preferably, the carbonate electrolyte is a mixture of ethylene carbonate and dimethyl carbonate, and the volume ratio of ethylene carbonate to dimethyl carbonate is 1:(0.5-1.5).

7. A method for preparing the electrolyte according to any one of claims 1 to 6, characterized in that: include: preparing modified inorganic nanoparticles containing vinyl groups and flame retardant groups containing PH bonds; The carbonate electrolyte, the modified inorganic nanoparticles, the polymerization monomer, the initiator and the lithium salt are mixed.

8. The preparation method according to claim 7, characterized in that: The preparation process of the modified inorganic nanoparticles comprises: firstly modifying inorganic nanoparticles with a vinyl-containing silane compound to obtain modified nanoparticles, and then using a flame retardant containing a PH bond to react with the vinyl groups on the modified nanoparticles to prepare the modified inorganic nanoparticles containing both vinyl groups and flame retardant groups with PH bonds; Preferably, the vinyl-containing silane compound is selected from at least one of acryltrimethoxysilane, methylacryltrimethoxysilane and vinyltrimethoxysilane, and the molar ratio of the inorganic nanoparticles to the vinyl-containing silane compound is 1:(0.01-0.035); Preferably, the molar ratio of the vinyl-containing silane compound to the flame retardant containing a PH bond is (1.5-3.0):1, more preferably (1.5-2.5):1; Preferably, the preparation process of the modified inorganic nanoparticles comprises: mixing the dried inorganic nanoparticles, the vinyl-containing silane compound and the first organic solvent, adjusting the pH value to 9-11, reacting at 65°C-80°C for 10h-15h, removing the first organic solvent after the reaction is completed to obtain the modified nanoparticles; mixing the modified nanoparticles, a flame retardant containing a PH bond and a second organic solvent, heating to 70°C-90°C to dissolve the flame retardant containing a PH bond, dripping an initiator solution into the reaction system for 1.5h-3.0h, continuing the reaction for 10h-15h, and removing the second organic solvent after the reaction is completed; More preferably, the first organic solvent is selected from at least one of anhydrous ethanol and anhydrous methanol; More preferably, the second organic solvent is selected from at least one of toluene and xylene; More preferably, the initiator solution is obtained by mixing an initiator and the second organic solvent, and the mass ratio of the initiator to the flame retardant containing a PH bond is (0.3-1.0):

100.

9. A method for preparing a lithium battery, characterized in that: include: Injecting the electrolyte described in any one of claims 1 to 6 or the electrolyte prepared by the preparation method described in any one of claims 7 to 8 into a battery cell, encapsulating it into a liquid battery, and heating the liquid battery; Preferably, during the heating process, the heating temperature is controlled to be 40°C-80°C, and the treatment time is 0.5h-10h; Preferably, the battery cell is assembled by stacking a positive electrode sheet, a separator and a negative electrode sheet; Preferably, the positive electrode active material on the positive electrode plate is a nickel-cobalt-manganese-lithium ternary material; Preferably, the isolation film is a PP film; Preferably, the negative electrode active material on the negative electrode plate is graphite.

10. A lithium battery, characterized in that: Prepared by the preparation method described in claim 9.